Gut microbiota mitigate the reproductive toxicity of silver nanoparticles through thiamine-derived metabolites - Jing-Xi Gong; Xin-Lei Wang; Chen-Xin Lin; Xin-Yuan Li; Jun Wu; Qiao-Guo Tan; Liuyan Yang; Ai-Jun Miao (Nature Communications)
Abstract The environmental and health risks of silver nanoparticles (AgNPs) have driven the development of numerous engineering strategies to reduce the likelihood of exposure. Nonetheless, AgNP exposure is often inevitable, prompting a search for effective detoxification strategies at the organism level. Given the critical role of the gut microbiota in host health, we test its ability to mitigate the adverse effects of AgNPs by introducing various bacterial strains into the Caenorhabditis elegans gut and then comparing the nematode’s response with that of germ-free nematodes. Reproduction, the most sensitive toxicity endpoint tested herein, is significantly impaired by AgNPs but is rescued by colonization with Pseudomonas mendocina. Gene expression analyses reveal that this bacterium suppresses both the initiating and key events within the adverse outcome pathways triggered by AgNPs. Metabolomic profiling of gut bacteria and AgNP-exposed nematodes followed by verification with standard substances identifies two thiamine-derived metabolites, 4-methyl-5-thiazoleethanol and thiamine monophosphate, as pivotal in reducing the reproductive toxicity of AgNPs. Our study presents a promising approach to mitigate the adverse effects of nanoparticle exposure, through manipulation of the gut microbiota.